2019
DOI: 10.1021/acs.jpcb.9b05768
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Dynamical Effects of Tyr32 Phosphorylation in K-Ras: Molecular Dynamics Simulation and Markov State Models Analysis

Abstract: Phosphorylation of tyrosine 32 in K-Ras has been shown to influence function by disrupting the GTPase cycle. To shed light on the underlying mechanism and atomic basis of this process, we carried out a comparative investigation of the oncogenic G12D K-Ras mutant and its phosphorylated variant (pTyr32) using all-atom molecular dynamics simulations and Markov state models. We show that, despite sharing a number of common features, G12D and pTyr32-G12D K-Ras exhibit some distinct conformational states and fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 48 publications
(87 reference statements)
5
30
0
Order By: Relevance
“…We also show that the mutants affect the binding site exposure to the solvent and the interactions with other amino acids, Tyr32 and Thr35, near the binding site. This may indicate that the mutants play a similar role in GTP hydrolysis as in K-Ras4A and K-Ras4B and other Ras proteins ( 41 , 58 , 59 , 60 , 61 ).…”
Section: Introductionmentioning
confidence: 89%
“…We also show that the mutants affect the binding site exposure to the solvent and the interactions with other amino acids, Tyr32 and Thr35, near the binding site. This may indicate that the mutants play a similar role in GTP hydrolysis as in K-Ras4A and K-Ras4B and other Ras proteins ( 41 , 58 , 59 , 60 , 61 ).…”
Section: Introductionmentioning
confidence: 89%
“…The previous works suggested that mutations signicantly affect the conformational alterations of the switch-I and switch-II in KRAS and change binding activity of KRAS to its regulators and effectors. [25][26][27][28][29][30][31][32][33] From residue substitutions at different sites, G12, G13 and Q61 mutations respectively account for 89%, 9% and 1% of the observed mutants of KRAS. 34 In addition, the effect of mutations at the other sites on the GTP-and GDP-KRAS binding were also investigated by different work groups.…”
Section: Introductionmentioning
confidence: 99%
“…phosphorylation alters the conformational dynamics of the KRAS protein 51 . Furthermore, the phosphorylation of WT-KRAS caused a substantial allosteric effects on the dynamics of the bound RAF1-RBD.…”
Section: Resultsmentioning
confidence: 99%
“…The details of each system are presented in Supplementary Table 3 . The MD simulations were conducted following previously published approaches with some modification 51 , 79 . At the preparation phase, each system was placed in a solvent-filled cube of TIP3P water molecules with a solvent padding size of 20 Å in each dimension.…”
Section: Methodsmentioning
confidence: 99%